VARIASI PEMBELAJARAN BAHASA INDONESIA MAHASISWA UNIVERSITAS BINA DARMA DI MASA PANDEMI - Indah Sari, Ayu Puspita; Mayrita, Hastari (Direktorat Riset dan Pengabdian pada Masyarakat (DRPM) Universitas Bina Darma, 2020)
This study aims to describe the variations in teaching lecturers, variations in assignments and inhibiting factors for learning Indonesian for Bina Darma University students during the pandemic using qualitative descriptive methods as well as through interviews and observations. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results showed: (1) The teaching variations of the lecturers were very diverse, which was adjusted to the mastery and skills of the lecturers in using IT to interact with students, such as using E-Learning, E-Mail, Zoom, Google Classroom, WhatsApp, Youtube content; (2) Variations in assignment are also very diverse according to the ability of lecturers to use IT; (3) External and internal factors are inhibiting factors for the variation of Indonesian Language learning among Bina Darma University Students during the Pandemic Period.